factores desencadenantes de la emigración en los habitantes del barrio riberas del jubones del cantón el guabo, año 2023 -2024 - Redrovan Duran, Melany Gissel; Mejia Fajardo, Juan Fernando (Machala, 2025)
The research "Triggering factors of emigration in the inhabitants of the Riberas del Jubones neighborhood of the El Guabo canton, year 2023-2024" has the general objective of determining the triggering factors of emigration in the inhabitants of the sector. In recent years, emigration has been considered a social problem that stems from the economic situation of people who are part of a family group, due to different triggering factors that influence the decision to emigrate to a country different from their place of origin; among the main factors are unemployment, poor academic preparation, domestic violence, high cost of the basic family basket of goods, and intrafamily problems. The factors that trigger emigration correspond to situations or conditions that are generated by certain social phenomena within a country and this can vary in the economy of the population, which represents a challenge in time and space for men and women of different ages who, faced with situations of conflict, unemployment, family instability and social problems, decide to leave their place of origin for other countries with the objective of obtaining work opportunities that allow them to improve their standard of living and that of their families. The research is based on the Socialist theory of Karl Marx, in the Social Interaction of Erving Goffman and in the Functionalist Structuralism of Talcott Parsons that allow understanding and identifying the situations that arise in the daily life of human beings for decision making, which are important in the future of them and the people who comprise their nuclear family. The epistemological approach is based on the empirical inductive and hypothetical deductive approach, the type of research is basic because a study is generated based on the analysis of the problem that allowed reaching the planted objectives, related to the triggering factors of emigration. The applied methodology approach is of mixed type, the methods used were Inductive and Deductive. The research instruments used were a survey of 120 people living in the Riveras del Jubones neighborhood and an interview with the president of the neighborhood and of the parish council of La Iberia parish. From the qualitative and quantitative results of the field research, it is determined that the problem of emigration lies mainly in the triggering factors that correspond to the socioeconomic situation, insecurity and intrafamily problems experienced by the inhabitants of the Ribera del Jubones neighborhood of the parish of La Iberia. Therefore, as a proposal, an entrepreneurship development program was proposed based on workshops on easy and quick activities to generate resources and improve the economic situation of the household, thus reducing the decision to emigrate to other countries in the presence of intra-family and economic problems. The proposal is aimed at strengthening intra-family relations and the socio-economic situation of the inhabitants of the Riveras del Jubones neighbourhood, considering that it is important for families to have an economic income in accordance with their needs and to seek short-term resources to cover household expenses, thus reducing the absence of the family member who emigrated to another country.
La investigación titulada "Factores desencadenantes de la emigración en los habitantes del barrio Riberas del Jubones del cantón El Guabo, año 2023-2024", plantea como objetivo general determinar los factores desencadenantes de emigración en los habitantes del sector. Durante los últimos años, la emigración es considerada un problema de carácter social que parte de la situación económica que padecen las personas que forman parte de un grupo familiar, debido a diferentes factores desencadenantes que incidieron en la decisión de emigrar hacia un país diferente de su lugar de origen; entre los principales elementos se menciona el desempleo, escasa preparación académica, violencia doméstica, elevado costo de la canasta básica familiar y problemas intrafamiliares. Los factores desencadenantes de emigración corresponden a situaciones o condiciones que se generan por ciertos fenómenos sociales dentro de un país y esto puede variar en la economía de la población, que representa un desafío en tiempo y espacio para hombres y mujeres de diferentes edades que ante situaciones de conflicto, desempleo, inestabilidad familiar y problemas sociales, deciden salir de su lugar de origen hacia otros países con el objetivo de lograr oportunidades laborales que permitan mejorar su nivel de vida y el de sus familias. La investigación se fundamenta en la teoría Socialista de Karl Marx, en la Interacción Social de Erving Goffman y en el Estructuralismo Funcionalista de Talcott Parsons que permiten comprender e identificar las situaciones que se presentan en el diario vivir del ser humano para la toma de decisiones, mismas que son importantes en el futuro de ellos y las personas que comprenden su núcleo familiar. El enfoque epistemológico se fundamenta en base al enfoque empírico inductivo e hipotético deductivo, el tipo de investigación es básica porque se genera un estudio en base al análisis del problema que permitió alcanzar los objetivos planteados, relacionados con los factores desencadenantes de la emigración. El enfoque de la metodología aplicada es de tipo mixta, los métodos utilizados fueron Inductivo y Deductivo. Cómo instrumentos de investigación se aplicó la encuesta a 120 personas que habitan en el barrio Riveras del Jubones y entrevista al presidente de la barriada y de la junta parroquial de la parroquia La Iberia. De los resultados cualitativos y cuantitativos de la investigación de campo, se determina que el problema de emigración radica principalmente en los factores desencadenantes que corresponden a la situación socioeconómica, de inseguridad y problemas Intrafamiliares que viven los habitantes del barrio Riveras del Jubones de la parroquia La Iberia. Por consiguiente, a modo de propuesta, se planteó un programa de desarrollo de emprendimiento en base a talleres sobre actividades fáciles y rápidas de realizar para generar recursos y mejorar la situación económica del hogar, de esta manera, se disminuye la decisión de emigrar a otros países ante la presencia de problemas Intrafamiliares y económicos. La propuesta se orienta al fortalecimiento de las relaciones Intrafamiliares y la situación socioeconómica de los habitantes del barrio Riveras del Jubones, considerando que es importante que las familias tengan un ingreso económico acorde a sus necesidades y busca generar recursos a corto plazo para solventar los gastos del hogar, de esta manera se disminuye un poco la ausencia del familiar que emigró a otro país.
Keywords: DESEMPLEO; EMIGRACION; FACTORES DESENCADENANTES; RELACIONES INTRAFAMILIARES; VIOLENCIA DOMESTICA